Epidemiological Study of Patients with Spinal Cord Injury Treated in POLEM, a Specialized Clinic in São Paulo State – Brazil - Lopes, José Eduardo de Andrade; Santos, Karl Alex Patteis dos; Machado, Caroline da Costa; Borges, Meire Cristina; Coelho, Eder Ferreira; Simões, Ìris Lino Kemp; Pereira, Ivone Mara; Dalera, Mariele Torricelli Brunelli; Bertazini, Talita Schneider de Camargo; Lopes, José Eduardo de Andrade (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Objective To analyze the epidemiological profile of patients with spinal cord injury treated at POLEM – Associação de Apoio às Pessoas com Lesão Medular (Association for Supporting People with Spinal Cord Injury).Method The population studied comprised 113 patients with spinal cord injury, of traumatic or nontraumatic etiology, and the data obtained were compared with those of other institutions.Results Of the 113 patients, 70.8% were male and 29.2% female. Traumatic lesions were responsible for 54% of the patients, and nontraumatic for 46%. Of the patients with traumatic injury, 90.2% were male, the main cause being traffic accidents. In nontraumatic lesions, women were the most affected, 51.9%; and dysraphism and myelitis were the main causes (31% and 21%, respectively).Conclusion The results showed an important incidence of spinal cord injury due to trauma, mainly affecting young individuals of productive age and low educational level, representing high economic and social costs. The data found in the present study are similar to those of other studies performed in our country.
Keywords: spinal cord injury; epidemiology; causes; rehabilitation